IDENTIFIKASI ASPEK GREEN MARKETING PADA OBYEK WISATA CANGING WATERFALL DALAM UPAYA MEWUJUDKAN PARIWISATA BERKELANJUTAN DI DESA SAMBANGAN KEC SUKASADA KAB BULELENG - Komang Budarsana; Ni Luh Henny Andayani; Nyoman Dini Andiani (Healing : Jurnal Pariwisata, 2026)
This study aims to analyze the implementation of the green marketing concept at Canging Waterfall Tourism Object based on the 4P marketing mix (product, price, place, and promotion) and to identify the supporting and inhibiting factors in its implementation to achieve sustainable tourism. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, documentation, and questionnaires. The research informants consisted of tourism managers, local community members, and visitors selected using purposive and accidental sampling techniques. Data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the implementation of green marketing at Canging Waterfall has been carried out gradually through the aspects of product, price, place, and promotion. The tourism product emphasizes natural authenticity, trekking trails, and environmentally integrated facilities. Pricing is affordable while supporting sustainable management and community empowerment.